Fostering Job Satisfaction: The Role of Communication Quality and Colleague Support in Job Involvement - Ratih Pratiwi (AKSES: Jurnal Ekonomi dan Bisnis, 2019)
This article aimed to discuss the effect of colleague support, communication quality on work engagement and job satisfaction in 100 human resources sharia hotels in Semarang. To answer hypotheses the data obtained being analysed with structural equation modeling using Partial Least Square (PLS) estimation. The support of colleagues has a significant influence on job satisfaction. Colleague support was found to be insignificant on work involvement. Communication quality has a significant influence on job satisfaction and job involvement. Work involvement does not have a significant effect on job satisfaction. To improve job satisfaction, it is necessary to improve the quality of communication, support from colleagues and work superiors by involving colleagues in various events conducted by the organization. This research does not consider increasing compensation such as awards and awards, as well as other retreats that might increase work engagement on job satisfaction. Keywords: Colleague Support; Communication Quality; Work Engagement; Job Satisfaction